CLONAGEM E EXPRESSÃO DO GENE xynB3 QUE CODIFICA A β-XILOSIDASE III NA BACTÉRIA AQUÁTICA Caulobacter crescentus - Bosetto, Adilson (2015)
The application of enzymes in industrial processes, in its broad sense, has shown the market evolution for innovative alternatives for preserving the environment. Brazil has a great potential to develop some technologies, which allow the use of such materials as substratum for products with higher added value, due to the large amount of lignocellulose as waste that comes from agriculture. Therefore, the analysis of genes expression related to microbial degradation of plant cell wall has caught the researchers attention, mainly because it is associated to the possibility of controlled large-scale synthesis of enzymes applied in biofuel production. In this context, the Gram-negative bacterium C. crescentus is found as a promising microorganism for biotechnological exploitation due to its ability on degrading xylan, the major component of plant hemicellulose. There are several genes in the bacterial genome that codify to Xylanases and β-Xylosidases. In order to purify and biochemically characterize the β-Xylosidase III protein of C. crescentus, xynB3 gene (CCNA_00856) that contains 1,623 nucleotides and encodes a protein with conserved domains of β-Xylosidase with 540 amino acid residues has been studied. Therefore, xynB3 gene was isolated from genomic DNA of C. crescentus NA1000 by Polymerase Chain Reaction (PCR) using specific primers. The single amplification product was cloned into pJet1.2Blunt vector in non-cohesive sites and reintroduced in vector of pTrcHisA expression within the reading frame to produce a histidine tag at the amino-terminus area of fusion protein. The obtained construction was denominated pTrcHis-xynB3 and the confirmation of its gene identification was figured out by the DNA sequence after insertion into the TOP10 E. coli strain and subsequent experimental tests of expression in different temperature of growth, IPTG concentrations and induction times. The recombinant protein was overexpressed into inclusion bodies, thus, in a non-soluble form. Different induction and purification protocols were used to obtain the β-xylosidase III pure of C. crescentus, in native or non-native form. However, assays of enzymatic activity with different substrates neither demonstrated β-xylosidase activity nor detectable levels of the protein. These results suggest that the enzyme was not active during the assays, due its expression in inclusion bodies. This suggests that this protein may have a toxic effect on E. coli when expressed at high levels. Thus, this trial contributes to additional data about the xylanolytic complex concerning the aquatic bacterium C. crescentus.